2018
DOI: 10.1097/wnf.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum MIYAIRI 588 as Adjunctive Therapy for Treatment-Resistant Major Depressive Disorder: A Prospective Open-Label Trial

Abstract: Aim Up to 60% of depressed patients do not obtain sufficient relief from a course of antidepressant therapy, and these treatment-resistant major depressive disorder (TRD) patients are at increased risk for relapse, chronicity, persistent psychosocial impairments, and suicide. Probiotics actively participate in treatment of neuropsychiatric disorders. However, the role of gut microbiota in brain disorders and depression remains unclear. We performed a prospective study to evaluate the effects of Clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 37 publications
2
106
0
1
Order By: Relevance
“…These treated mice also showed upregulated central 5-HT, BDNF and GLP-1 receptors in the brain (Sun et al, 2018). Remarkably, the combination of C. butyricum with antidepressants reduced depression in about 70% of treatment-resistant MDD patients, of which 30% achieved remission (Miyaoka et al, 2018). These studies support the antidepressive efficacy of non-pathogenic C. butyricum.…”
Section: Clostridium Butyricumsupporting
confidence: 58%
“…These treated mice also showed upregulated central 5-HT, BDNF and GLP-1 receptors in the brain (Sun et al, 2018). Remarkably, the combination of C. butyricum with antidepressants reduced depression in about 70% of treatment-resistant MDD patients, of which 30% achieved remission (Miyaoka et al, 2018). These studies support the antidepressive efficacy of non-pathogenic C. butyricum.…”
Section: Clostridium Butyricumsupporting
confidence: 58%
“…It also reduced the inflammatory, immune and oxidative markers and mitochondrial stress via implicating PPAR-γ pathway. This mood illness has been improved when patients were treated with synbiotics [ 196 ], probiotics of multiple strains ( L. acidophilus , L. casei and B. bifidum ) [ 197 ], L. rhamnosus HN001 [ 198 ], and C. butyricum [ 199 ], and probiotic mixture [ 200 ]. In addition, supplements such as polyunsaturated fatty acids (PUFAS), especially eicosapentaenoic acid (EPA), and folate-based N-acetlycysteine are the strongest adjunctive treatment for depressive disorder [ 201 ].…”
Section: Interaction Of Gut and Nervous System: Gut–brain Axismentioning
confidence: 99%
“…Furthermore, every study demonstrated a significant, quantitatively evident, decrease/improvement of symptoms and/or biochemically relevant measures of anxiety and/or depression for probiotic or combined prebiotic–probiotic use. This is observed regardless of the specific probiotic, method of administration or length of trial, across all test cohorts, irrespective of depression severity or additional comorbidities 20–26. The current evidence indicates: prebiotics are unlikely to be effective as an isolate therapy for depression within the timeframes investigated21 25; probiotics may be useful agents20–26; concomitant prebiotic–probiotic therapy may also be useful, though it is not obvious whether these agents function synergistically from this cohort of studies 21 25.…”
Section: Discussionmentioning
confidence: 87%
“…The 17 item Hamilton Depression Rating Scale (HAM-D-17) and Beck Depression Inventory II (BDI-II) were the two most commonly employed methods for evaluating subjects’ psychiatric condition pre/during/post invention. Probiotic/combined prebiotic–probiotic therapy significantly reduced patient scores on these tests in 6/7 studies 21–26. The exception, Rudzki et al ,20 found no link between probiotic use and changes in HAM-D-17 scores.…”
Section: Discussionmentioning
confidence: 95%